Book I Come to Boone - Williams, David Cratis (Appalachian State University, 1999)
Following his retirement in 1976 from a distinguished career as a teacher and administrator at Appalachian State University in Boone, North Carolina, Cratis Williams wrote these memoirs of his life odyssey from a log cabin in eastern Kentucky to the upper echelons of American education.